Health-related quality of life and associated factors in Chinese menstrual migraine patients: a cross-sectional study - Wenxiu Luo; Xing Cao; Jiayu Zhao; Jiaming Yang; Yu Cen; Jinlong He; Jing Luo; Yunling Zhong; Ying Luo; Xinyue Wang; Liqiu Yang; Xingyu Feng; et al. (BMC, 2022)
Abstract Background Menstrual migraine is a particular form of migraine with a significant impact on the quality of life for women afflicted. Presently, no study has reported the quality of life in menstrual migraine patients. This work aims to assess the health-related quality of life and identify its associated factors among Chinese menstrual migraine patients. Methods The cross-sectional study group consisted of 109 patients with menstrual migraine, and the control group consisted of 397 female patients with non-menstrual migraine. In total, 506 patients completed questionnaires for demographic and clinical information, the Self-rating Idea of Suicide Scale, the Hamilton Depression Scale, the Hamilton Anxiety Scale, the Headache Impact Test-6, the Perceived Social Support Scale, the Pittsburgh Sleep Quality Index. Health-related quality of life was measured using the 36-Item Short Form Survey. Results Compared with non-menstrual migraine patients, five dimensions of health-related quality of life were all found to be significantly impaired in menstrual migraine patients. Headache frequency (ß = − 0.218, P = 0.014), the impact of headache on daily life (ß = − 0.270, P = 0.002), depression symptoms (ß = − 0.345, P < 0.001) were significantly associated with physical component summary, depression symptoms (ß = − 0.379, P < 0.001), social support (ß = 0.270, P < 0.001), suicidal ideation (ß = − 0.344, P < 0.001) were closely related to mental component summary. Conclusion Menstrual migraine patients had a significantly poorer health-related quality of life in many domains than non-menstrual migraine patients. Headache frequency, the impact of headache on daily life, depression symptoms, social support, and suicidal ideation were significantly associated with health-related quality of life in menstrual migraine patients. Trial registration: ChiCTR1800014343. This study was registered prospectively on 7 January 2018 at Chinese Clinical Trial registry. http://www.chictr.org.cn/showproj.aspx?proj=24526